Methanethiol Abundance and Oxidation in a Polluted Marine Atmosphere - Charel Wohl; Grant L. Forster; Pete M. Edwards; Parvadha Suntharalingam; David E. Oram (Geophysical Research Letters)
Abstract Biological activity in the surface ocean leads to emissions of methanethiol (MeSH) and dimethyl sulfide (DMS). Measurements of MeSH in the marine atmosphere are sparse and the impact of NOx pollution on MeSH oxidation remains unexplored. We present measurements of MeSH and DMS at a coastal site with NOx up to 24.3 ppb in the United Kingdom during May and June. Winds coming from the seaward (northerly) direction showed a median (25th quantiles) MeSH mixing ratio of 15.7 (7.9–26.9)  ppt. The measurements reveal significantly lower MeSH during daytime. Atmospheric box model calculations suggest that ∼25% of the MeSH oxidation is initiated by NO3 at this site and that NOx pollution can reduce the SO2 yield from MeSH. This work is further evidence for the prevalence of MeSH and illustrates the impact of NOx pollution on MeSH oxidation with associated implications for its role in aerosol‐cloud processes, and climate.